Analysis of the Effect of Government Expenditures on School Enrollment in Pakistan - Muhammad Idrees; Farah Khan; Muhammad Sufian Bin Omar Fauzee (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2021)
Purpose: No one can deny the importance of education as it not only improves living standard but also promotes self-esteem as well as improves social development. The role of the government cannot be overlooked in the development of education. Therefore, the main purpose of this study is to analyses the role of government through national income and government expenditure on education through school enrolment in Pakistan. Design/Methodology/Approach: We have used secondary data over the period of 2000 to 2017 for empirical analysis.  We used descriptive statistics analysis, and the method of least squares is used to obtain empirical results.  Findings: The result shows that national income and government expenditures have positive effects on school enrollment, indicating when national and government expenditures increase, ultimately school enrolment also increases in the country. Implications/Originality/Value: Our results of this study suggest that national income needs to be increases and government spending also needs to be increases in order to improve education in the country.